2018
DOI: 10.1186/s42408-018-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-wildfire recovery of an upland oak−pine forest on the Cumberland Plateau, Kentucky, USA

Abstract: Background: Many forests within the southern Appalachian region, USA, have experienced decades of fire exclusion, contributing to regeneration challenges for species such as oaks (Quercus spp. L.) and pines (Pinus spp. L.), and threatening the maintenance of oak-dominated forests in the future. While the use of prescribed fire as a forest management tool is increasing within this region, there remains a lack of information on the potential role of wildfire. A wildfire within the Daniel Boone National Forest, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 35 publications
2
25
1
Order By: Relevance
“…1). Prescribed fires ignited on similar ridgetops in the Cumberland Plateau have been low intensity (Blankenship and Arthur 2006), although high-severity fire can occur in drought conditions (Black et al 2018). Also, because we calculated scarring rates based on all samples present, regardless of their recorder status, our scarring rate estimates were lower than in studies that used only recorder trees to calculate the percentage of samples scarred.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1). Prescribed fires ignited on similar ridgetops in the Cumberland Plateau have been low intensity (Blankenship and Arthur 2006), although high-severity fire can occur in drought conditions (Black et al 2018). Also, because we calculated scarring rates based on all samples present, regardless of their recorder status, our scarring rate estimates were lower than in studies that used only recorder trees to calculate the percentage of samples scarred.…”
Section: Discussionmentioning
confidence: 98%
“…Both species have a suite of fire adaptations that include thick bark, root collar sprouting after topkill, improved seed germination on mineral soil or partial litter, and seedbeds and seedling establishment in high light or low competition environments (Lawson 1990, Little andGarrett 1990,). In long-unburned stands, thinning and repeated fires (Guldin 2007) or high-intensity fire (Jenkins et al 2011;Black et al 2018) have been shown to promote natural yellow pine regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our findings, Barden and Woods (1976) and Vose et al (1994) provide evidence that pine recruitment in the southern Appalachians was substantially higher after high-severity fire due to increased mortality of competing, shade-tolerant or mesophytic tree species, relative to sites with no fire or low-severity surface fires. Black et al (2018) also documented higher shortleaf pine sapling recruitment at sites that burned more intensely in the Cumberland Mountains of eastern Kentucky. In contrast to Hite Fork, less frequent fire over the last 40 years at Wall Fork promoted recruitment of mesophytic tree species at the expense of pines, providing evidence for ongoing "mesophication" (Nowacki and Abrams 2008).…”
Section: Discussionmentioning
confidence: 82%
“…In recent decades, prescribed fire has increasingly been used as a management tool to reduce shade-tolerant or mesophytic tree cover, promote oak and pine regeneration, diversify wildlife habitat, and manage forest fuels in oak and mixed pine-oak forests across the CHF (e.g., Brose et al 2001;Waldrop 2014). Recent studies have shown that repeated burning (multiple fires within 10-20 years) can reduce shade-tolerant or mesophytic tree abundance (Blankenship and Arthur 2006;Izbicki et al 2020;Borden et al 2021) and promote oak (Hutchinson et al 2012;Brose et al 2013) and pine recruitment (Barden and Woods 1976;Black et al 2018), but these effects can be variable and dependent on landscape position and pre-fire forest structure (Alexander et al 2008;Arthur et al 2015). Other factors, such as the timing and severity of prescribed fire, can also influence its effects.…”
Section: Introductionmentioning
confidence: 99%
“…One study compared CBI with canopy fire severity indices by examining the relationships between fire disturbance and the composition of tree species in a burned area; the results showed that CBI can better explain the effects of fire severity on species composition (Johnstone et al 2010). Many fire ecology studies have used CBI to quantify fire severity and to explain the effects of fire severity on biomass, density, and seedling turnover of several dominant species (Black et al 2018).…”
Section: Quantifying Fire Severity With a Composite Burn Index (Cbi)mentioning
confidence: 99%